The Incidence of Chronic Energy Deficiency in Pregnant Women at Borong Public Health Center - Desiman, Natalia Veranda; Syamruth, Yendris Krisno; Riwu, Ruth Rosina (Faculty of Public Health, Nusa Cendana University, 2022)
Chronic Energy Deficiency (KEK) is one of the issues that might arise during pregnancy when the intake and nutritional demands are out of balance. The Upper Arm Circumference (LiLA) of pregnant women less than 23.5 cm is used to determine Chronic Energy Deficiency (KEK). The goal of this study is to analyze the variables linked to Chronic Energy Deficiency (KEK) in pregnant women in the Borong Health Center's working area in East Manggarai Regency. This type of research quantitative research uses a cross-sectional study approach. This research was conducted in the working area of ​​the Borong Health Center with a sample of 56 pregnant women. The data analysis used was univariable and bivariable analysis with a chi-square statistical test. The results of this study indicate that there is a relationship between the variables of maternal age (p = 0.037), and the close relationship (-0.315), mother's occupation (p = 0.036) and the close relationship (-0.320), family income (p = 0.001) and the close relationship namely (0.474), gestational distance (p = 0.000) and the close relationship (0.559), energy intake (p = 0.017) and the close relationship (0.356), and protein intake (p = 0.001) and the close relationship (0.488) with the incidence of KEK in pregnant women in the working area of ​​the Borong Health Center. Meanwhile, factors that were not related to the incidence of KEK in pregnant women in the working area of ​​the Borong Health Center were the mother's level of knowledge (p = 0.244), the mother's education level (p = 0.136), and parity (p = 1,000). The conclusion is that there is a relationship between maternal age, mother's occupation, family income, pregnancy distance, energy intake, and protein intake with the incidence of CED. Pregnant women are expected to receive health education in pregnant women classes to prepare for pregnancy or counseling about nutritional needs before pregnancy and during pregnancy